Climatological Analysis of Extratropical Cyclones’ trajectories formed in the Antarctic Peninsula region - Gandra, Mariana Monteiro dos Santos; Quadro, Mário Francisco Leal de (Ciência e Natura, 2020)
Cyclones play an important role in the general circulation of the atmosphere, enabling the meridional transport of excess heat, humidity and momentum from low latitudes to high latitudes. In the Southern Hemisphere, the area between southern Brazil and the Peninsula Antarctica (AP) is described as one of the most favorable for the formation of cyclones (30°S to 70°S) due to the existence of strong temperature gradient between the ocean and the surface air layer above the ocean and also because of pre-existing baroclinic instabilities. This study is associated with the Project ATMOS (AnTarctic Modeling Observation System) and explored the role of extratropical cyclones in teleconnections between high and medium latitudes to track the trajectories of extratropical cyclones that are formed in the Antarctic Peninsula (AP) and move towards the central sector of the South Atlantic. The analysis of the tracked trajectories showed that the cyclones reached the central sector of the South Atlantic during the months of autumn (greater number) and winter (greater displacement), while the statistical analysis indicated that the intensity of the cyclones is more linearly linked to the mean sea level pressure field than to Superficial Sea Temperature Anomalies. Os ciclones desempenham um papel importante na circulação geral da atmosfera, possibilitando os transportes meridionais de calor, umidade e momentum excedentes das baixas latitudes para altas latitudes. No Hemisfério Sul, a área entre o sul do Brasil e a Península Antártica (PA) (30° S a 70° S) é descrita como uma das mais favoráveis para a formação de ciclones devido à existência de fortes contrastes de temperatura entre o oceano e a camada de ar em superfície e também instabilidades baroclínicas pré existentes. Este estudo está associado ao Projeto ATMOS (AnTarctic Modeling Observation System) e explorou o papel dos ciclones extratropicais (CE) nas teleconexões entre as altas e médias latitudes, em que o objetivo foi rastrear as trajetórias daqueles que se formaram ...